Investigation of the Effect of Agarose Gel Concentration and Culture Period on Bio and Mechanical Properties of Chondrocyte Tissue Engineering - Jawad, Akram (Physics and Chemistry of Solid State, 2021)
As a gel scaffold for chondrocyte tissue engineering, agarose concentration plays a significant role in the relationship between porosity and nutrition. In this work, the effect of concentration and period cultured on Glycosaminoglycan (GAG) and mechanical properties have been studied. A bovine chondrocytes have been isolated and seeded in different agarose gel scoffed concentrations, about 4% and 6%, for different period cultured, 0 and 7 days. The MTS machine and Spectrophotometric with calibration curve method were used to measure mechanical properties, and GAG concentration of the prepared samples, respectively. The results of mechanical tests and GAG contents shown that there are a wide range of dispersion in the most of the samples, which attribute to different factors. For mechanical properties, these factors could be attributed to anisotropic of the produced chondrocyte with agarose scaffolds, insufficient cells' dispersion within the gel scaffold during seeding and cultured time, and some test procedure condition, such as EBSS hydration. While for GAG results, those factors could be the differences of the cell growth environment between in-vitro and in vivo media.